(untitled) (Ágora de Heterodoxias, 2016)
The objective of the research study that originated this work was to identify how the entrepreneurial attitude in college students is constituted. We worked with 1072 persons, aged between 22 and 25 years, all of them were in the last three semesters of the various degree programs offered at Oriente of University, Venezuela. We applied a questionnaire about entrepreneurial attitude, structured as an attitude scale of Likert format which consisted on 25 questions and a response pattern that moved from the options totally agree to totally disagree. The data were studied through a factorial analysis, by analyzing their main components. The results showed an index of internal consistency that is equivalent to an alpha of 0.89 with a probability of 0.01. It was concluded that the entrepreneurial attitude is formed by five dimensions which are the critical sense of responsibility, achievement motivation, self-efficacy in job performance, resilience in meeting goals, and the perception towards business opportunities.